ANALISIS SISTEM DAN PROSEDUR PENERIMAAN RETRIBUSI DAERAH DI KABUPATEN MINAHASA SELATAN SESUAI DENGAN PERMENDAGRI NOMOR 13 TAHUN 2006 TENTANG PEDOMAN PENGELOLAAN KEUANGAN DAERAH - Aldy, Watupongoh Risky; Sondakh, Jullie J; Mawikere, Lidia (Universitas Sam Ratulangi, 2019)
Regional Levy Income is a part of Regional Original Income that can support regional revenues in accordance with regional regulations (Perda) issued by local governments. The purpose of this study was to determine the system and procedures for receiving regional levies in South Minahasa regency in accordance with Permendagri Number 13 of 2006. The analytical method used was descriptive analysis, while analysis of systems and procedures was carried out by comparing concepts, theories and regulations in the implementation of the system and procedures for receiving regional levies specifically with the provisions of Permendagri Number 13 of 2006. The results of the study obtained that in general the System and Procedure for Regional Retribution in South Minahasa is in accordance with PERMENDAGRI Number 13 of 2006 concerning regional financial management guidelines.